Penggunaan Experience Based Learning Pada Pembelajaran Sejarah Kebudayaan Islam Untuk Meningkatkan Kesadaran Beragama dan Daya Kritis Siswa MAN di Kabupaten Bekasi - Yasir Amrullah; Supiana; Sulasman; Setia Gumilar (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2020)
[THE USE OF EXPERIENCED-BASED LEARNING IN LEARNING ISLAMIC CIVILIZATION HISTORY TO IMPROVERELIGIOUS AWARENESS AND STUDENTS' CRITICAL THINKING AT MADRASAH ALIYAH NEGERI IN BEKASIREGENCY]. The purpose of this study was to identify: The use of Experience-Based Learning (EBL) in learningSKI so as to foster students' religious awareness and critical power of MAN students in Bekasi Regency; This study uses a quantitative approach methods. The method used is a quasy experiment. The results of this study includes: 1) The use of EBL in learning SKI to foster religious awareness of students of MAN Bekasi Regency, it is known from the difference in the average questionnaire before learning in the experimental and control group meeting 1 of 3.60, after learning it was obtained 6.85; meeting 2 showed a greater mean difference of 10,075; and meeting 3 of 4.85. This means that H1 = i1 ≠ i2 is accepted so that there is a significant difference between the experimental class and the control class in cultivating religious awareness; The use of EBL in learning SKI to grow students' critical power can be seen from the results of the average difference between the pre test experimental class with treatment and the control class meeting 1 of 4.75, after treatment shows a greater difference between the post test experimental class and the control class of 10,875. Meeting 2 shows the difference in the average post test experimental class with control of 10,125, and meeting 3 is 9.25. This means that H1 = i1 ≠ i2 so that there is an average difference between the experimental class and the control class in growing the critical power of MAN students in Bekasi Regency